2018
DOI: 10.1186/s13750-018-0115-5
|View full text |Cite|
|
Sign up to set email alerts
|

Online tools supporting the conduct and reporting of systematic reviews and systematic maps: a case study on CADIMA and review of existing tools

Abstract: Systematic reviews and systematic maps represent powerful tools to identify, collect, evaluate and summarise primary research pertinent to a specific research question or topic in a highly standardised and reproducible manner. Even though they are seen as the "gold standard" when synthesising primary research, systematic reviews and maps are typically resource-intensive and complex activities. Thus, managing the conduct and reporting of such reviews can become a time consuming and challenging task. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
168
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(215 citation statements)
references
References 30 publications
(24 reference statements)
0
168
0
12
Order By: Relevance
“…With one exception, all suggested tools were analyzed: CADIMA (Kohl et al, 2018), Covidence 6 (Veritas Health Innovation), DistillerSR 7 (Evidence Partners), Endnote 8 (Clarivate tice guidelines in medicine. The Cochrane 3 organization facilitates and ensures high quality SRs in clinical research and public health, which are achieving high societal impacts.…”
Section: Sr Tools Analyzedmentioning
confidence: 99%
See 1 more Smart Citation
“…With one exception, all suggested tools were analyzed: CADIMA (Kohl et al, 2018), Covidence 6 (Veritas Health Innovation), DistillerSR 7 (Evidence Partners), Endnote 8 (Clarivate tice guidelines in medicine. The Cochrane 3 organization facilitates and ensures high quality SRs in clinical research and public health, which are achieving high societal impacts.…”
Section: Sr Tools Analyzedmentioning
confidence: 99%
“…Several articles have compared different SR tools before (e.g., Kohl et al, 2018;Marshall et al, 2014). However, these focus on the complete SR and provide little detail on the screening phase.…”
Section: Introductionmentioning
confidence: 99%
“…To formulate our search and screening protocols, we follow the guidelines of the Collaboration for Environmental Evidence (2018), and use the free online platform CADIMA to perform the screening phase (Kohl et al 2018).…”
Section: Systematic Literature Review Approachmentioning
confidence: 99%
“…Training a machine‐learning algorithm with a subset of include/exclude decisions allows the algorithm to prioritize relevant papers and estimate when all relevant studies have been found. Automated data extraction is currently less developed as an off‐the‐shelf functionality, but is currently implemented in a few software packages (e.g., colandr; see also Kohl et al ; Westgate et al ).…”
Section: Challenges and Opportunities For Greater Use Of Srs And Evidmentioning
confidence: 99%